2014
DOI: 10.1007/s12559-014-9301-0
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Learning for Air Pollution by Meta-Cognitive Online Sequential Extreme Learning Machine

Abstract: Many time series problems such as air pollution index forecast require online sequential learning rather than batch learning. One of the major obstacles for air pollution index forecast is the data imbalance problem so that forecast model biases to the majority class. This paper proposes a new method called meta-cognitive online sequential extreme learning machine (MCOS-ELM) that aims to alleviate data imbalance problem and sequential learning at the same time. Under a real application of air pollution index f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…However, among these primary studies, there is sufficient evidence that SLR studies on data preprocessing are lacking, as indicated by the fact that only 2% of the primary studies considered in this study followed SLR guidelines. This finding [136] N P N Y 1.5 [105] N N N Y 1.0 [86] N Y N Y 2.0 [137] N N N Y 1.0 [106] N P N Y 1.5 [83] N Y N Y 2.0 [138] N P N Y 1.5 [139] N P N Y 1.5 [140] N N N Y 1.0 [68] N Y N Y 2.0 [141] N P N Y 1.5 [142] N P N Y 1.5 [67] N P N Y 1.5 [90] N P N Y 1.5 [50] N P N Y 1.5 [53] N N N Y 1.0 [52] N P N Y 1.5 [47] N P N Y 1.5 [48] N N N Y 1.0 [143] N P N Y 1.5 [117] N Y N Y 2.0 [144] N N N Y 1.0 [145] N P N Y 1.5 [73] Y Y Y Y 4.0 [146] N P N Y 1.5 [147] N P N Y 1.5 [148] N N N Y 1.0 [149] N P N Y 1.5 [150] N P N Y 1.5 [60] N P N Y 1.5 [151] N N N Y 1.0 [152] N P N Y 1.5 [153] N N N Y 1.0 [154] N N N Y 1.0 [155] N N N Y 1.0 [156] N N N Y 1.0 [157] N N N Y 1.0 [158] N P N Y 1.5 [159] N N N Y 1.0 [160] N N N Y 1.0 [161] N N N Y 1.0 [162] N N N Y 1.0…”
Section: What Are the Limitations Of Current Research?mentioning
confidence: 99%
“…However, among these primary studies, there is sufficient evidence that SLR studies on data preprocessing are lacking, as indicated by the fact that only 2% of the primary studies considered in this study followed SLR guidelines. This finding [136] N P N Y 1.5 [105] N N N Y 1.0 [86] N Y N Y 2.0 [137] N N N Y 1.0 [106] N P N Y 1.5 [83] N Y N Y 2.0 [138] N P N Y 1.5 [139] N P N Y 1.5 [140] N N N Y 1.0 [68] N Y N Y 2.0 [141] N P N Y 1.5 [142] N P N Y 1.5 [67] N P N Y 1.5 [90] N P N Y 1.5 [50] N P N Y 1.5 [53] N N N Y 1.0 [52] N P N Y 1.5 [47] N P N Y 1.5 [48] N N N Y 1.0 [143] N P N Y 1.5 [117] N Y N Y 2.0 [144] N N N Y 1.0 [145] N P N Y 1.5 [73] Y Y Y Y 4.0 [146] N P N Y 1.5 [147] N P N Y 1.5 [148] N N N Y 1.0 [149] N P N Y 1.5 [150] N P N Y 1.5 [60] N P N Y 1.5 [151] N N N Y 1.0 [152] N P N Y 1.5 [153] N N N Y 1.0 [154] N N N Y 1.0 [155] N N N Y 1.0 [156] N N N Y 1.0 [157] N N N Y 1.0 [158] N P N Y 1.5 [159] N N N Y 1.0 [160] N N N Y 1.0 [161] N N N Y 1.0 [162] N N N Y 1.0…”
Section: What Are the Limitations Of Current Research?mentioning
confidence: 99%
“…However, when applying these methods in practical tasks, their performance has not always been acceptable because of their imbalanced training sets, i.e., because of the skewness of the sample distribution across classes. In many practical disciplines, including chemical and biomedical engineering [1], financial engineering [2], environmental sciences [3] and information technology [4], rare events, also referred to as abnormal behaviors, are of great importance. Therefore, it is critical to reduce the influence of the bias introduced from training sets on the detection of rare events.…”
Section: Introductionmentioning
confidence: 99%
“…In ICDM'05, CIL problem has also been listed into the Top 10 challenging problems in data mining [8]. During the past two decades, CIL problem has been observed in a lot of real-world applications, including fraud detection [9], [10], network intrusion detection [11], [12], disease diagnosis [13], [14], software defect detection [15], [16], industrial manufacturing [17], Bioinformatics [18], [19], environment resource management [20], and security management [21], etc.…”
Section: Introductionmentioning
confidence: 99%